Study on heterogeneous traffic flow characteristics of a two-lane road - Sharma, Nitish; Arkatkar, Shriniwas S.; Sarkar, Ashoke K. (Transport, 2011)
The paper presents traffic studies conducted by using a video capturing technique on the uninterrupted heterogeneous mix of vehicles plying on an undivided two-lane road facility. On the basis of the collected data, traffic characteristics pertaining to arrival, headway and speed distributions have been plotted considering suitable mathematical distributions to fit field observed values. The curves representing fundamental traffic flow relationships among three basic variables, namely speed, density and flow have also been established. Thus, a systematic attempt to enable the understanding of heterogeneous traffic flow parameters has been made through this exploratory study. First published online: 07 Jul 2011